Endoscopic retrograde cholangiopancreatography - Moon, Jong Ho; Choi, Hyun Jong; Lee, Yun Nah (Endoscopy, 2014)
New technological developments in endoscopic retrograde cholangiopancreatography (ERCP) for diagnosis and treatment have been slow to progress. However, several informative study results were presented during the 2014 Digestive Disease Week (DDW; 3 – 6 May; Chicago, Illinois, USA) in specific ERCP areas, such as prevention of post-ERCP pancreatitis using nonsteroidal anti-inflammatory drugs and pancreatic duct stenting. Novel and interesting study results regarding preoperative stent selection for periampullary tumors, metal stents for hilar stricture or for prevention of duodenal reflux, and intraductal biliary tumor ablation using photodynamic therapy or radiofrequency ablation were discussed. Study results presented at the meeting regarding single-operator cholangioscopy using the SpyGlass system or direct peroral cholangioscopy have indicated the possibility of future development. Results using peroral pancreatoscopy and confocal laser endomicroscopy for biliary lesions, including strictures, were also presented.